Irrigation management effects on nitrate leaching and mowing requirements of tall fescue - Chabon, Joshua D. (Kansas State University, 2014)
Irrigation management may influence nitrate leaching under tall fescue (Festuca arundinacea) and also affect its mowing requirements. Two experiments were conducted on tall fescue growing on a Chase silt loam soil near Manhattan, Kansas. Each experiment was arranged in a split-plot design, with irrigation treatments applied to whole plots: 1) frequency-based irrigation, water was applied three times weekly to deliver a total of 19 mm water wk⁻¹ regardless of weather conditions; and 2) soil moisture sensor (SMS)--based irrigation, 34 mm of water was applied when soil dried to a predetermined threshold. In the first experiment, sub-plots consisted of unfertilized turf, and N applied as urea or polymer-coated urea at 122 and 244 kg ha⁻¹ yr⁻¹. Suction lysimeters at a 0.76 m depth were used to extract nitrate leachate bi-monthly. Turf quality was rated weekly. In the second experiment, subplots were mown at 5.1 cm or 8.9 cm, based upon the 1/3 rule, with or without monthly applications of the growth regulator trinexapac-ethyl (TE). Data were collected on total mowings and visual turf quality. Soil moisture sensor-based irrigation resulted in water savings of 32 to 70% compared to frequency-based irrigation. Leaching levels did not exceed 0.6 mg L⁻¹ and no differences in leaching were observed between irrigation treatments or among N sources. All fertilized turf had acceptable quality throughout the study. In the second experiment, irrigation strategy did not influence total number of mowings. In the first year, TE application reduced total mowings by 3 in tall fescue mowed at 5.1 cm, but only by 1.5 when mowed at 8.9 cm. In the second year, mowing at 8.9 vs. 5.1 cm or using TE vs. not resulted in a 9% reduction in total mowings each. The SMS-based irrigation saved significant amounts of water applied compared to frequency-based irrigation, while maintaining acceptable quality, but irrigation treatments did not affect nitrate leaching or mowing frequency in tall fescue on fine silt-loam soil. Nitrate leaching, regardless of amount, was well below the standards set for human health (10 mg L⁻¹). Applications of TE are more beneficial for turfgrass mowed at lower cutting heights.
Keywords: Irrigation; Turfgrass; Leaching; Mowing; Plant growth regulator; Agronomy (0285)